(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the efficiency of pneumatic transport device designed for the transportation of cotton in the cotton industry. The material carrying capacity of a pneumatic tube depends on its diameter, pipe material, flow rate, aerodynamic properties of the cotton and the design of the pipe inlet. It is recommended to manufacture the pipe inlet in the form of a cone, which helps to reduce its aerodynamic resistance, increase the throughput capacity of the pipeline and use pipes of a smaller diameter relative to the existing one.